PENINGKATAN PENGETAHUAN MASYARAKAT KELURAHAN RUMBAI BUKIT KECAMATAN RUMBAI KOTA PEKANBARU MENGENAI PENYELESAIAN SENGKETA JUAL BELI TANAH BERDASARKAN KITAB UNDANG- UNDANG HUKUM PERDATA - Suhendro .; Andrew Shandy Utama; Ade Pratiwi Susanti (LPPM Universitas Abdurrab, 2019)
The problem of partners in community service activities is the lack of knowledge of the community of Rumbai Bukit Village, Rumbai District, Pekanbaru City regarding the settlement of disputes over land sale and purchase based on the Civil Code. The solution offered in this community service activity is to increase the knowledge of the community of Rumbai Bukit Village, Rumbai District, Pekanbaru City regarding the settlement of land purchase disputes based on the Civil Code. The implementation method used in community service activities is to use lecture, dialogue and discussion methods in order to provide legal counseling to the public. Partner participation in community service activities is to provide time, provide a place and supporting facilities, and present the community as participants of the activity. The output target of this community service is scientific articles that have been submitted and will be published in non-accredited national journals. The conclusion is that this activity has been successfully implemented and the benefits can be felt directly by the participants. This can be seen from the answers of the participants in the questionnaire given after the activity was carried out. After the activity was carried out, 88% of the participants answered that they knew the material presented. His suggestion is that the activities with this theme should be carried out not only to the people of Rumbai Bukit Village, but also to other urban communities in the Rumbai District of Pekanbaru City.